2012
DOI: 10.1007/s10404-012-0987-6
|View full text |Cite
|
Sign up to set email alerts
|

A microgrooved membrane based gas–liquid contactor

Abstract: This research presents an approach for applying microgrooved membranes for improved gas-liquid contacting. The study involves analysis of the performance of the microdevice by quantifying the flux enhancement for different membrane configurations. Two kinds of configurations, continuous and non-continuous grooves, were investigated. The microgrooves provide shear-free gasliquid interfaces, which result in local slip velocity at the gas-liquid interface. Exploiting this physical phenomenon, it is possible to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…4 Various studies have been performed to address the inuence of wall slip on interfacial transport in electro-osmotic ows, [4][5][6][7] in thin lm evaporation in microchannels, 8 and in heat and mass transfer through permeable surfaces. [9][10][11][12][13] It is found that the concentration polarisation at membrane walls decreases with increasing slip, which results in higher interfacial mass transfer rates. 10,[14][15][16] In general, all these studies report a signicant amplication of the transport process under consideration in the presence of a slippery interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Various studies have been performed to address the inuence of wall slip on interfacial transport in electro-osmotic ows, [4][5][6][7] in thin lm evaporation in microchannels, 8 and in heat and mass transfer through permeable surfaces. [9][10][11][12][13] It is found that the concentration polarisation at membrane walls decreases with increasing slip, which results in higher interfacial mass transfer rates. 10,[14][15][16] In general, all these studies report a signicant amplication of the transport process under consideration in the presence of a slippery interface.…”
Section: Introductionmentioning
confidence: 99%
“…However, slippage can be increased signicantly by micro-structuring of the hydrophobic surface with posts, grooves, or cavities that are positioned transversely, longitudinally, or obliquely to the main ow direction. 13,[23][24][25][26][27][28][29][30][31] As gas is entrapped in these micro-structures, the liquid is in contact with a heterogeneous gas-solid interface characterised by partial slip conditions. Measured apparent or effective slip lengths on such superhydrophobic surfaces range from 10 0 to 10 2 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such micropatterns will promote turbulent flow due to increased surface roughness and hence mass transfer coefficient. 14 Micropatterns on ceramic surfaces have been conducted by various techniques such as replication. 15 anodization, 16 hydrothermal methods, 17 soft lithography, 18 laser carving, [19][20][21] chemical etching, 22 or powder blasting with the help of PDMS mask.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike these methods, Wessling et al [32] proposed a unique method called phase separation micro-molding (PSµM). The polymer solution was cast into a microgrooved mold and then immersed in a coagulation bath.…”
Section: Introductionmentioning
confidence: 99%